The Etymology of Abbreviations in English and Tajik Diplomatic Terms - Iskandar , Khodzhaev (IJLHE: International Journal of Language, Humanities, and Education, 2022)
The article is devoted to one of the important problems of the linguistics the problem of term and terminology. During the research from the etymology of abbreviations point of view we discovered that the majority of etymology of abbreviations in English and Tajik diplomatic terms has their specific lexical features of lexical units of abbreviations and identification of the main ways and features of their translation.